Goal effectiveness after players` dismissals in professional futsal teams - Gómez, M. A.; Méndez, C.; Indaburu, A.; Travassos, B. (Journal of Sports Sciences, 2019)
The purpose of this study was to analyse the effect of players` dismissals on the outcome of attacks in elite futsal matches, and to establish the performance profile of the attacks made in numerical superiority by elite futsal teams. One hundred and twenty five attacking game situations in numerical superiority (dismissal of opponents from defensive team) were analysed from the regular season of the Spanish professional Futsal League. The effect of contextual-related variables (quality of opposition, match-location, match-periods, opponent team`s fouls, match-status, attack-duration and match-type) on goal effectiveness was analysed using binomial logistic regression and two-step cluster analysis. Results from the binary logistic regression showed that the highest attack effectiveness was achieved when the teams play at home, perform the attack during minutes 33-36 and the opposing team has 3 fouls. Secondly, the two-step cluster analysis technique allowed identifying four types of attacks when the teams were playing with numerical superiority. The results showed the great importance (in order) of match-type, match-status, attacking team`s fouls, match-period, quality of opposition, opposing team`s fouls, match-location, goal situation, and attack duration. The identified trends may help coaches to design the superiority/inferiority scenarios more specifically during training and to monitor them during competition.